CONCENTRATIONS OF METALS AND TRACE ELEMENTS IN DIFFERENT TISSUES OF NINE FISH SPECIES FROM THE MEĐUVRŠJE RESERVOIR (WEST MORAVA RIVER BASIN, SERBIA) - Đikanović, Vesna; Skorić, Stefan; Gačić, Zoran (Archives of Biological Sciences, 2016)
Element concentrations in selected fish species from different trophic levels were analyzed. The following fish species were analyzed: common nase (Chondrostoma nasus), roach (Rutilus rutilus), freshwater bream (Abramis brama), barbel (Barbus barbus), Prussian carp (Carassius gibelio), chub (Squalius cephalus), European perch (Perca fluviatilis), wels catfish (Silurus glanis) and northern pike (Esox lucius). Fish were collected from the Međuvršje Reservoir (West Morava River Basin, western Serbia) during 2012, and samples of liver, muscle and gills were analyzed for As, B, Ba, Cd, Co, Cr, Cu, Fe, Hg, Li, Mn, Mo, Ni, Pb, Sr, and Zn using inductively coupled plasma optical emission spectrometry (ICP-OES). The liver and gills had the highest measured element concentrations, with Cu, Zn, Fe and Sr being the most prominent. The bioaccumulation of metals was species-specific, with the accumulation exhibiting the following trends: Prussian carp > northern pike > freshwater bream > European perch > chub > common nase > barbel > roach > wels catfish; Li>Pb>Zn>Cu>Fe>Ba>Mn>Sr>Cr>As>Mo>Ni>B, in all examined species; for Co, Cd and Hg, the bioaccumulation factor (BAF) was 0. Results of this study point to the tissue-specific differences in element concentrations, and to distinct differences between fish species regarding the accumulation patterns: common nase, with the highest accumulation observed in the liver, and Prussian carp, with the highest accumulation observed in the gills. DOI: 10.2298/ABS151104069D Key words: fish; metal bioaccumulation; trace element concentration; water reservoir; gills Received: November 4, 2015; Revised: January 15, 2016; Accepted: January 15, 2016; Published online: August 5, 2016 How to cite this article: Đikanović V, Skorić S, Gačić Z. Concentrations of metals and trace elements in different tissues of nine fish species from the Međuvršje reservoir (West Morava River Basin, Serbia). Arch Biol Sci. 2016;68(4):811-9.